ANALISIS RASIO KEUANGAN PT. PEGADAIAN (PERSERO) TAHUN 2019-2021 - Aditya (2022)
Financial ratio analysis is an activity that shows the mathematical relationship between one amount and another. The use of analytical tools in the form of company ratios can determine whether the company's financial position is good or bad based on standard comparison ratios. Seeing developments in the business world that is getting tighter, causing increased competition between companies. For this reason, the company must be able to survive and even grow and develop properly, namely by paying attention to the condition of the company and adapting to faster technological advances. To find out how the state of a company is needed a good analysis, so that the company can make the right decisions. The purpose of this final project is to understand, study and know the financial performance of PT. Pegadaian (Persero) in 2019-2021 based on financial ratio analysis consisting of liquidity, activity, solvency and profitability ratios using indicators in the Decree of the Minister of State-Owned Enterprises KEP-100/MBU/2002. The results of this paper will determine the health of the company's performance in each of its financial position.